ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU PADA UD. MIE STEVEN KAROMBASAN KOTA MANADO - Megawati ., Sengkeunaung; Tommy F. Lolowang; Nordy F.L. Waney (AGRI-SOSIOEKONOMI, 2017)
This research aims to analyze raw material inventory at UD. Mie Steven. This research was conducted for four months from January to April 2017. The data used in this research are primary and secondary data. Primary data obtained through interviews with the company, while secondary data obtained from data that has been compiled in the form of documents from the company, data from BPS, previous research or from the internet. The data is processed using EOQ (Economic Order Quantity) method. The result of the research is known that the policy of raw material inventory control is done by UD. Mie Steven is not efficient yet. This is shown by the company's inventory cost is bigger than the result of analysis using EOQ method is 6,693 Kg with total cost of economical inventory Rp.11.325.500.